KnowEval: A Tool for Supporting Knowledge Transfer Evaluation - Ferreira Junior, José Wilson Cavalcanti; Ferreira, Williby; Saraiva, Juliana; Soares, Sérgio (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2025.11170, 2025)
The evaluation of Knowledge Transfer (KT) processes is essential for promoting organizational learning, enhancing operational efficiency, and fostering innovation. However, existing tools described in the literature offer limited support to organizations in this area. In general, knowledge about these tools remains unsystematized, lacks empirical validation, and is not widely adopted in practice. This article presents an overview of the key features of KnowEval, a decision support tool designed to recommend appropriate processes for KT evaluation based on strategic input variables. Furthermore, we describe the structured and dynamic database that enables the continuous integration of new evaluation processes. Finally, we present the validation results of KnowEval, using scenarios derived from an exploratory review of the literature. Video Available on:  https://zenodo.org/records/15485087